Integrated approach for management of root-knot nematode (Meloidogyne incognita) in bitter gourd (Momordica charantia) - SINGH, SATYENDRA (The Indian Journal of Agricultural Sciences, 2019)
Field trials were conducted to manage root-knot nematode (Meloidogyne incognita) infesting bitter gourd (Momordica charantia L.). Four summer ploughings in May-June, 2014 at 15Â±2 days interval caused 67% reduction in M. incognita population. To develop an ecofriendly nematode management module organic amendment (neem cake, Azadirachta indica at 1.5 t/ha) and talc based preparations of bio-agents (Pseudomonas flourescens and Trichoderma harzianum) as seed treatment (10 g/kg) and soil application (10 kg/ha) were integrated with summer ploughings as pre-treatment. Carbofuran 3G at 1 kg a.i./ha was kept as control. The treatments were: T1- Control (Carbofuran); T2- Neem cake; T3- P. flourescens (seed treatment (10 g/kg seed as well as soil application at 10 kg/ha); T4- T. harzianum (seed treatment 10 g/kg seed as well as soil application at 10 kg/ha); T5- T2+T3+T4; T6-Farmersâ€™ practice. The best protection of bitter gourd root-knot disease was achieved through integrated application of neem cake, P. flourencens and T. harzianum. Significantly better results (in terms of vine height and reduction in M. incognita population) were recorded under consequent second year trial (84 and 94% respectively) as compared to first year trial (47 and 73% respectively). It also enhanced marketable yield of bitter gourd significantly (P>0.5) (up to 108%) in the second season trial, as compared to farmersâ€™ practice. It is suggested that integrated approach using organic amendment with bioagents to manage root-knot disease of bitter gourd under natural infestation is environmental friendly and beneï¬cial to growers/farmersâ€™ having small holdings of land.